DISTINGUISHING BETWEEN SCIENCE AND SCIENTISM - Christin Christin (INTEGRAL, 2013)
Issues of conflict between science and faith/religion have existed for a long time. Some of the topics that have become the source of the conflicts are: The Evolution Theory and The Big Bang Theory which are assumed to be in contra with the creation story, which is generally believed by people of faith. The other controversial issue concerns the existence of God as a supernatural being. Even though in Indonesia these issues are viewed to be taboo, the hot debate between the atheist scientists and religious people in academic spheres occurs openly in some countries. However, do we have to choose between believing in science or believing in God? Which is the reliable source of truth?  This writing discusses the epistemology of science and its strength as well as its limitation as a body of knowledge.  The author is trying to describe scientism as an invalid worldview that leads to misunderstandings and conflict’s myths between faith and science.Keywords: Faith and science, scientism, reproducibility and clarity.Isu-isu pertentangan antara sains dan keimanan atau agama sudah bukan merupakan hal baru. Beberapa topik yang menjadi sumber konflik diantaranya: Teori Evolusi  dan Teori Ledakan Besar yang dianggap bertentangan kisah penciptaan, yang diyakini sebagai kebenaran yang diyakini oleh kelompok agamawan pada umumnya.  Topik lainnya adalah perdebatan  tentang bukti keberadaan Tuhan Allah sebagai pribadi supernatural. Walaupun di Indonesia hal ini masih dianggap tabu, perdebatan yang sengit antara kelompok ilmuwan ateis dan agamawan di kalangan akademisi terjadi secara terbuka di beberapa negara tertentu. Apakah kita harus memilih salah satu saja diantara: sains atau iman kepada Tuhan? Manakah yang  lebih dapat diandalkan sebagai sumber kebenaran? Tulisan ini membahas epistemologi dan kekuatan sains sekaligus keterbatasannya sebagai disiplin ilmu. Penulis juga mencoba memaparkan  kekeliruan paham saintisme, yang menyebabkan kesalahpahaman dan mitos pertentangan antara iman dengan sains.Kata Kunci: iman dan sains, dapat direproduksi, kejelasan.